(untitled) (Linguistics in Amsterdam, 2018)
Information structure has been suggested to be impaired in autistic populations, as they have consistently been found to experience difficulties with pragmatics and prosody (Eigsti et al. 2011; DePape et al. 2012). Therefore, the present study investigated the prosodic realization of focus by 37 Dutch children with autism spectrum disorder (ASD), in comparison with 29 typically developing (TD) children. The data, which we retrieved from the CHILDES database, were elicited in a structured storytelling task administered by Kuijper et al. (2015). Three acoustic measures were analyzed â accent type, pitch range and duration â , as these all have been associated with focus marking in Dutch (Gussenhoven 1983; Chen 2007, 2011; DePape et al. 2012). In addition, we looked at the position of accent placement within the sentence. The results show that even though in both groups children are more likely to produce a falling accent type to mark focus in sentence final position than in initial or medial position, this preference is significantly weaker for children diagnosed with ASD. However, the ASD group was not significantly different with regard to pitch range, duration or accent placement.